A non-invasive continuous cuffless blood pressure estimation using dynamic Recurrent Neural Networks. (15th December 2020) - Senturk, Umit; Polat, Kemal; Yucedag, Ibrahim
Highlights: Dynamic neural networks are used to estimate cuffless blood pressure. Folded and branched Recurrent Neural Networks (LSTM-NN and NARX-NN) were compared. Facilitates the use of blood pressure measurement with wearable technologies. Blood pressure estimation is performed for sequential time series signals. Abstract: Cardiovascular diseases (CVD) have become the most important health problem of our time. High blood pressure, which is cardiovascular disease, is a risk factor for death, stroke, and heart attack. Blood pressure measurement is commonly used to limit blood flow in the arm or wrist, with the cuff. Since blood pressure cannot be measured continuously in this method, the dynamics underlying blood pressure cannot be determined and are inefficient in capturing symptoms. This paper aims to perform blood pressure estimation using Photoplethysmography (PPG) and Electrocardiography (ECG) signals that do not obstruct the vascular access. These signals were filtered and segmented synchronously from the R interval of the ECG signal, and chaotic, time, and frequency domain features were subtracted, and estimation methods were applied. Different methods of machine learning in blood pressure estimation are compared. Dynamic learning methods such as Recurrent Neural Network (RNN), Nonlinear Autoregressive Network with Exogenous Inputs Neural Networks NARX-NN and Long-Short Term Memory Neural Network (LSTM-NN) used. Estimation results have been evaluated with performance criteria. Systolic Blood Pressure (SBP) error mean ± standard deviation = 0.0224 ± (2.211), Diastolic Blood Pressure (DBP) error mean ± standard deviation = 0.0417 ± (1.2193) values have been detected in NARX artificial neural network. The blood pressure estimation results are evaluated by the British Hypertension Society (BHS) and American National Standard for Medical Instrumentation ANSI/AAMI SP10: 2002. Finding the most accurate and easy method in blood pressure measurement will contribute to minimizing the errors.